PEMIKIRAN IBNU MISKAWAIH (RELEGIUS-RASIONAL) TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN ERA MODERN - Ahmad Saka Falwa Guna (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
This research is based on things that happen in society, there are still much disgraceful behavior, immoral acts, widespread drug use, murder, persecution, human rights violations, lack of honesty, and so on. This indicates that education has not achieved the expected goals. Where one of the goals of education is to create human beings with noble character. The focus of research is on Ibn Miskawaih's thoughts on education and the relevance of education in the modern era. The purpose of this study was to determine Ibn Miskawaih's thoughts on education and its relevance to education in the modern era. Ibn Miskawaih is one of the leaders of Islamic education.This research is in the research library research category. The research method is to collect the sources of books, writings, journals, articles, opinions of Ibn Miskawaih's thoughts. The descriptive-analytic method was used after the data on Ibn Miskawaih's thoughts were collected and analyzed.In conclusion, Ibn Miskawaih saw the importance of education and the environment for humans to facilitate the process of moral development. Ibnu Maskawaih stated that there are times when there is a change of heart, so it takes sharia, teachings of customs, and advice regarding manners. Therefore, humans with their minds can distinguish and choose what to do and what not to do. Ibn Miskawaih's thinking in education rests on the human concept and moral education.